2017
DOI: 10.1103/physrevb.96.155432
|View full text |Cite
|
Sign up to set email alerts
|

Optically induced Lifshitz transition in bilayer graphene

Abstract: It is shown theoretically that the renormalization of the electron energy spectrum of bilayer graphene with a strong high-frequency electromagnetic field (dressing field) results in the Lifshitz transition -the abrupt change in the topology of the Fermi surface near the band edge. This effect substantially depends on the polarization of the field: The linearly polarized dressing field induces the Lifshitz transition from the quadruply-connected Fermi surface to the doubly-connected one, whereas the circularly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 44 publications
0
31
0
1
Order By: Relevance
“…In the simplest case of a circular path of radius k (0) , the Berry phase defined in Eq. In contrast, the constant-energy cut for dispersions (26) with angular dependence (27) has an elliptic shape, as it shown in Fig. 4 (a).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In the simplest case of a circular path of radius k (0) , the Berry phase defined in Eq. In contrast, the constant-energy cut for dispersions (26) with angular dependence (27) has an elliptic shape, as it shown in Fig. 4 (a).…”
Section: Discussionmentioning
confidence: 87%
“…[15][16][17][18][19][20][21][22] Considerable effort has been given to find a way to generate topological insulator properties in such systems under irradiation 12,23,24 Optical dressing can also alter the tunneling and conductance 25 properties of a topological insulator, leading to tunable spin transport on their surfaces 26 with potential applications in spintronics, as well as result in an optically-stimulated Lifshitz transition. 27 Another important property of such electronic dressed systems for operating an optoelectronic device is the challenge of confining such electron states in a specific region. This is directly related to the presence or absence of the so-called Klein paradox 28 in the considered material.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that laser-illuminated graphene monolayers 14,18,23,37 and bilayers [38][39][40] may host chiral edge states if the laser parameters are appropriately chosen 41 . These Floquet chiral edge states will be the 'substrate' on which we will base our proposal.…”
Section: Hamiltonian Model and Floquet Solution Schemementioning
confidence: 99%
“…For α = λ = 0, the Hamiltonian [equation (2.7)] is similar to the bilayer graphene irradiated with circularly polarized light [35][36][37][38]. In the bilayer graphene irradiated with circularly polarized light, the light induces a term which is valley and polarization dependent.…”
Section: )mentioning
confidence: 99%